MAKNA FILOSOFIS JAJA WAYANG PADA UPACARA NGATURANG BERKATAN DI DESA PAKRAMAN BESTALA KECAMATAN SERIRIT KABUPATEN BULELENG - Putu Subawa (Genta Hredaya: Media Informasi Ilmiah Jurusan Brahma Widya STAHN Mpu Kuturan Singaraja, 2018)
Jaja Wayang use ceremony as a means of conducting Ngaturang Berkatan ceremony inPakraman Bestala Village, Seririt District, Buleleng Regency. This ceremony is very importantto be examined because the actualization of society with obedient to implement it but not yetunderstand tattwa and the meaning contained in the ceremony. The method used is through aphenomenological approach that is to observe natural phenomena or phenomena of social nature,the type of data in this study is qualitative data. In this study used several methods of datacollection such as: (1) Observation, (2) Interview (Interview); (3) Documentation Study.Presentation of research result in this research is descriptive method with attention to quality ofproblem discussed. Basic consideration of the use of jaja wayang at Ngaturang Berkatan ceremonyin Desa Pakraman Bestala is (1). As a concrete step in maintaining the natural balance, (2). It isBhakti form to Ida Sang Hyang Widhi Wasa, (3). As a form of media development of creativityand cultural preservation The process of using jaja wayang ceremony at Ngaturang Berkatanceremony is (1). Ngaturang piuning pretend, (2). Carry out updates, (3). Implementation of jointprayer, (4). Ngerauhang Process, (5). Nyineb. The meaning is to make the Hindus in the villageof Bestala who has a spiritual noble in order to achieve the goal of a prosperous life.